Linear‐selective hydroformylation of vinyl ether using Rh (acac)(2, 2′‐bis{(di[1H‐indol‐1‐yl]phosphanyl)oxy}‐1, 1′‐binaphthalene) – Possible way to synthesize 1, 3‐propanediol. (19th July 2020) - Wan, Kefeng; Zhao, Jiangui; Qin, Song; Zheng, Xueli; Fu, Haiyan; Li, Ruixiang; Chen, Hua; Yang, Jijun; Yang, Chunji
Abstract : Three bidentate phosphoramidite ligands were synthesized, characterized, and employed in Rh‐catalyzed hydroformylation of vinyl ethers. The complex Rh(acac)(2, 2′‐bis{(di[1H‐indol‐1‐yl]phosphanyl)oxy}‐1, 1′‐binaphthalene} (acac = acetylacetone) (Rh‐L4 ) was also synthesized and characterized. Rh‐L4 showed good regioselectivity for the hydroformylation of vinyl ethers under mild reaction conditions: 2 MPa of syngas, 1:1 (H2 /CO) substrate/catalyst molar ratio 1000:1, and 60 °C. The linear selectivity was up to 98%, and in most cases was about 80%, with no hydrogenation product formation observed, which could be a potential way to synthesize 1, 3‐propanediol. A mechanism study including density functional theory computational analysis showed that both Rh–H and CO insertion steps in the hydroformylation of vinyl ether were linear‐preferred in our catalyst system. Abstract : The highest linear‐selective (up to 98%) hydroformylation of vinyl ether among the existing reports. We achieved high atomic economy under mild reaction condition with branched aldehyde as the only by‐product. A mechanism study by density‐functional theory computation explained how steric hindrance influenced regioselectivity.